Theory of Financial Management in Practice of Czech Companies - Kuběnka, Michal; Honková, Irena (My University, 2016)
This article is focused on comparing of theoretical financial management approaches with financial management practice of Czech companies operating in sectors of manufacturing industry. Empirical research found big differences between basic theoretica recommandations and their fulfillment in practice. Discound rate in the form of weighted average cost of capital value plays a key role in many financial decisions above all in capital structure optimalisation and in dynamic assessment method needed for investment decisions. Nevertheless is proved that only 20 % of companies work with discount rate, the rest of them does not specify the discount rate value. It has been determined the impact of the ownership links with larger companies on the use of discount rate in company. This proves the fact that discount rate users are parent companies (15 %), daughter companies owned by Czech parent companies (27%) and daughter companies with foreign parent companies (54 %).
Teorie finančního managmentu v praxi českých společností
Keywords: Financial Management; WACC; discount rate; capital structure; investment assessment; manufacturing industry; Finanční management; WACC; diskontní sazba; kapitálová struktura; investiční ohodnocení; zpracovatelský průmysl